Greenness around schools associated with lower risk of hypertension among children: Findings from the Seven Northeastern Cities Study in China. (January 2020) - Xiao, Xiang; Yang, Bo-Yi; Hu, Li-Wen; Markevych, Iana; Bloom, Michael S.; Dharmage, Shyamali C.; Jalaludin, Bin; Knibbs, Luke D.; Heinrich, Joachim; Morawska, Lidia; Lin, Shao; Roponen, Marjut; et al.
Abstract: Evidence suggests that residential greenness may be protective of high blood pressure, but there is scarcity of evidence on the associations between greenness around schools and blood pressure among children. We aimed to investigate this association in China. Our study included 9354 children from 62 schools in the Seven Northeastern Cities Study. Greenness around each child's school was measured by NDVI (Normalized Difference Vegetation Index) and SAVI (Soil-Adjusted Vegetation Index). Particulate matter ≤ 1 μm (PM1 ) concentrations were estimated by spatiotemporal models and nitrogen dioxide (NO2 ) concentrations were collected from air monitoring stations. Associations between greenness and blood pressure were determined by generalized linear and logistic mixed-effect models. Mediation by air pollution was assessed using mediation analysis. Higher greenness was consistently associated with lower blood pressure. An increase of 0.1 in NDVI corresponded to a reduction in SBP of 1.39 mmHg (95% CI: 1.86,  −0.93) and lower odds of hypertension (OR = 0.76, 95% CI: 0.69, 0.82). Stronger associations were observed in children with higher BMI. Ambient PM1 and NO2 mediated 33.0% and 10.9% of the association between greenness and SBP, respectively. In summary, greater greenness near schools had a beneficial effect on blood pressure, particularly in overweight or obese children in China. The associations might be partially mediated by air pollution. These results might have implications for policy makers to incorporate more green space for both aesthetic and health benefits. Graphical abstract: Image 1 Highlights: Evidence on the association between greenness and blood pressure among children is scarce. We are the first to explore this topic based on school surrounding greenness exposure. Attending schools with higher greenness showed beneficial effects on blood pressure. The beneficial effects were stronger in children with higher BMI levels. Air pollution might partially mediate the effects of greenness on blood pressure. Abstract : Greater greenness near schools was associated with lower blood pressure among children, which might have implications for policy makers to incorporate more green space.